Development of antipeptide enzyme-linked immunosorbent assay for determination of gelatin in confectionery products - Tukiran, Nur Azira; Ismail, Amin; Mustafa, Shuhaimi; Hamid, Muhajir (Wiley-Blackwell, 2016)
The gelatin sources have become a controversial issue with regard to religious and health concern. Thus,the aims of this study were to develop and evaluate the efficiency of polyclonal antibodies against peptide immunogen of collagen a2 (I) chain for determination of gelatin sources in confectionery products by competitive indirect enzyme-linked immunosorbent assay (ELISA). Collagen a2 (I) chain protein showed resistance against heat treatment and detectable in certain commercial products when analysed by sodium dodecyl sulphate–polyacrylamide gel electrophoresis (SDS-PAGE). The established ELISA exhibited low cross-reactivity to fish and chicken gelatin. The IC50 value was 0.39 lg mL 1, and the limit of detection (IC10) was 0.05 lg mL 1. There were no false-positive results from forty-eight commercially processed products. The present method is useful for determination of gelatin in confectionery products.